2021
DOI: 10.37766/inplasy2021.6.0090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined Cognitive and Exercise Interventions on Post-stroke Cognitive Function: A Systematic Review and Meta-analysis

Abstract: Review question / Objective: To investigate the cognitiveexercise the combined interventions reported in the research literature, and synthesize their effectiveness in improving cognitive function poststroke. Information sources: We systematically searched the PubMed and Cochrane Library electronic databases and clinical trial registration websites, and screened clinical randomized controlled trials published in peer-reviewed journals. INPLASY registration number: This protocol was registered with the Internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…For primary index measurement, we found that, relative to the CT, CMDT training led to a significant improvement in global cognitive function, as measured by MMSE and MoCA, by the end of the 4 week intervention. This result is consistent with findings from recent meta-analyses of CMDT training ( 12 , 22 ). It shows that CMDT training has more advantages than single-cognitive training in improving cognitive impairment.…”
Section: Discussionsupporting
confidence: 93%
“…For primary index measurement, we found that, relative to the CT, CMDT training led to a significant improvement in global cognitive function, as measured by MMSE and MoCA, by the end of the 4 week intervention. This result is consistent with findings from recent meta-analyses of CMDT training ( 12 , 22 ). It shows that CMDT training has more advantages than single-cognitive training in improving cognitive impairment.…”
Section: Discussionsupporting
confidence: 93%